2021
DOI: 10.1002/jum.15857
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Endovaginal Ultrasound Proficiency and Learning Curve Among Emergency Medicine Trainees

Abstract: Objectives Performing and interpreting endovaginal ultrasound is an important skill used during the evaluation of obstetric and gynecologic emergencies. This study aims to describe the level of proficiency and confidence achieved after performing 25 endovaginal examinations. Methods This is a prospective study at a single urban academic emergency department. Participants performed a minimum of 25 endovaginal ultrasounds under the supervision of a point‐of‐care ultrasound expert. Anatomical structures were iden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(24 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Derr et al (6) observed that emergency physicians needed at least 25 exams in point-of-care ultrasound training to acquire proficiency in adequate preparation and insertion of the endovaginal transduc- Self-made transvaginal ultrasound simulator: new training equipment in ultrasound evaluation of controlled ovarian stimulation and oocyte retrieval er, identification of the bladder and uterus, and anatomic relationships of pelvic organs. However, the authors found that emergency physicians still had difficulty identifying the ovaries after this initial training, suggesting that a learning curve persisted after 25 exams (6) . Several authors have highlighted the importance of simulator training to improve ultrasound skills in obstetrics and gynecology.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Derr et al (6) observed that emergency physicians needed at least 25 exams in point-of-care ultrasound training to acquire proficiency in adequate preparation and insertion of the endovaginal transduc- Self-made transvaginal ultrasound simulator: new training equipment in ultrasound evaluation of controlled ovarian stimulation and oocyte retrieval er, identification of the bladder and uterus, and anatomic relationships of pelvic organs. However, the authors found that emergency physicians still had difficulty identifying the ovaries after this initial training, suggesting that a learning curve persisted after 25 exams (6) . Several authors have highlighted the importance of simulator training to improve ultrasound skills in obstetrics and gynecology.…”
Section: Discussionmentioning
confidence: 99%
“…Future specialists traditionally acquire their new skills while assisting actual patients, under the direct supervision of a more experienced professional. However, this form of training may increase the patients' risks to injuries and it is associated with varied levels of treatment success; real-life training also requires a long period of mentoring, resulting in a slow learning curve and high training costs (4)(5)(6) .…”
Section: Introductionmentioning
confidence: 99%
“…1,7,[9][10][11][12][15][16][17][18][19]22 Most authors defined novices as individuals without any prior POCUS experience, while one group defined novices as having completed fewer than 10 POCUS examinations. 1,7,[9][10][11][12][15][16][17][18][19]22 Three studies (17.6%) involved learners with variable experience with inclusion criteria for studies ranging from a minimum of 30 exams performed to >60 exams performed. 13,14,21 One study (5.9%) included learners of mixed experience, and one (5.9%) did not specify the level of prior POCUS experience.…”
Section: Characteristics Of Learners and Educationmentioning
confidence: 99%
“…15 Derr et al found that endovaginal ultrasound skills plateaued before 20 examinations, with slightly different plateaus for specific skills; 10 exams for preparation and insertion and 16 exams for identification of the ovaries. 9 Clunie et al also assessed airway and endovaginal ultrasound. Anesthesiology residents failed to reach a predetermined definition of competency for both airway and endovaginal ultrasound; however, only 8 examinations were performed.…”
Section: Learning Outcomesmentioning
confidence: 99%
“…After a 1-hour didactic session, a written examination, and 10 supervised studies, the residents were able to perform a TVUS examination to evaluate for IUP with good concordance with the ED director of ultrasound 10 . Learners continued to benefit from performing a greater number of TVUS exams and felt confident after performing 25 examinations 11 .…”
Section: Tvus Is a Teachable Skillmentioning
confidence: 99%